Para uma Prática de Interculturalidade no Processo de Ensino-Aprendizagem do Francês, como Língua Estrangeira, em Moçambique: O Método de Tradução do Conto Tradicional Macua, na 12ª Classe, na Escola Secundária de Nampula - Pedro, Rafael (2006)
French language is one of the taught subjects, not only on the secondary school curriculum, but also at university, in Mozambique. The syllabus of this subject has been designed with regard to a geographical and socio-cultural framework, which does not match with Mozambican learners. It is spoken about France and the French who designed the textbook, which is used as teaching material in the secondary school in Mozambique. This textbook bridges information, which is unfamiliar to Mozambican learners of French. The aim of teaching and learning French in Mozambique, at school level, is to have learners achieve proficiency in this language in order for them to be able to communicate in various circumstances at school, university and elsewhere. The Mozambican learner, therefore, should be able to read, understand, write discourses related to school, university and elsewhere life, in his/her daily life, bearing in mind that most literature is in French. This research employs the translation method of macua tale as a cultural text in the process of teaching and learning French, the driving force in the cultural signification of learning and in the acquisition of communicative competence. The pedagogic experiment of this method and the interviews carried out teachers of French have revealed that learners can achieve linguistic competence necessary to be a successful grade 12 certificate holder in the final nation-wide examinations